(3TQM bUjOI GdHQOI ddHhUjQis - (3GdbGVi HMQ Hf QFjS Hf UdGM Hf NdjaI Hf Ydj GdgGQhfi GdeGdcjs; (3eMeO Hf SYjO Hf MeGO GdUfgGLj GdHhUjQj, (B696 (3g`,J (B696 (3g` s
(3ChdgG (B:s
(3hHYO aEfg jbhd GdYHO GdabjQ HMQ Hf QFjS Ef HYV ENhGfi SCdfi Cf CYed dbUjOg GdHhUjQi s
(3BNQgG (B:s
(3hHjJ JNab GdCQhGM ajg CMH Edi ef bUQ efHa Je GdcJGH , HMeO Gddg s
(3ai BNQgG Jedc HJGQjN (B1200(3g` hHBNQ UaMGJgG JYbjHg hHgG CKGQ QWhHgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B11s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B167 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1332s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYg eOjfI GdYde , GdcGXejg (B_ (3HZOGO (B(472) s
Keywords: (3GdCOHs